Communication, Strategic Moves, and Commitment: An Analysis from the Experimental Economics - Palacio Garcia, Luis Alejandro; Díaz Pérez, Brayan Snehider (Universidad Pedagógica y Tecnológica de Colombia, 2022)
Thomas Schelling is one of the most important references in game theory and negotiation, as he has been recognized as a pioneer in proposing the concepts and laying the foundations of formal models, always based on observation and empirical contrast. His focus on communication, strategic moves and commitment makes it possible to understand the advantages, in terms of bargaining power, of publicly announcing that the decision has been made, even when the message is cheap talk. Taking this starting point, this article focuses on how experimental economics has expanded and refined its original proposals. It is possible to classify this literature into three aspects: 1) non-binding communication, 2) use of strategic moves, 3) credibility and commitment. Among the findings, it is highlighted that communication is a useful mechanism for transmitting private information and, therefore, affects the beliefs and behavior of negotiators. For their part, strategic moves play a role since they transfer the advantage of the first move to the second player. Finally, the sense of justice, fear of punishment, and the reputation of negotiators affect the credibility of their threats.